PENGARUH PEMUPUKAN FOSFAT DAN KALIUM TERHADAP PERTUMBUHAN DAN HASIL GABAH PADI HITAM DI SAWAH TADAH HUJAN - Heny Kurnia, Nyemas; Sasli, Iwan; Wasian, Wasian (Politeknik Negeri Ketapang, 2021)
Black rice (Oriza sativa.L) is one of the local varieties that has a high anthocyanin content within the pericarp layer of the seed, which contains nutritions that are important to health. Local black rice seed frequently empty with grain, caused by ineffective manure, especially potassium and phosphate. Utilization of rainfed areas for black rice cultivation can be done with balanced fertilization. This study aims to determine the effect of phosphate and potassium fertilization on the growth and production of black rice grain in rainfed areas. The study used a Completely Randomized Design (CRD) model with two factors, i.e KCl fertilizer factor consisting of four levels namely k0 without treatment, k1 = 20 g / plot, k2 = 40 g / plot, k3 = 60g / plot and the second factor was phosphate consisting of the four levels, i.e p0 without treatment, p1 = 20 g / plot, p2 = 40 g / plot, p3 = 60g / plot. Each treatment was repeated three times so that there were 48 experimental plot units. The results showed that there was an interaction between the treatments on the weight of 1000 grains while the application of potassium fertilizer significantly affected the number of productive tillers, harvested unhusked rice, milled unhusked rice and the weight of 1000 grains. The application of phosphate fertilizer only significantly affected the number of productive tillers with recommended doses 40g / plot because it gives a higher yield compared to the others in the number of 17.95 productive tillers